Eksplorasi Air Tanah di Pandaan - Roh Sanstoso Budi Waspodo (Jurnal Keteknikan Pertanian, 2011)
Abstract This geoelectricity survey was conducted to get an idea of the distribution of resistivity (rock resistivity) either vertically or laterally, especially the alleged distribution of layers of rock can serve as carriers of water layer or aquifer. The results of this survey are expected to provide data to the PT Sampoerna, about the possibilities of layout, the existence and depth of carrier layers of water that can be used to meet the supply water for the needs of the Integrated Education Trainning Center. The results of the geoelectricity measurements were generally cannot reach the target depth to be surveyed, where, from the 10 points of sounding wich were conducted, only 3 points could penetrate the >100 m depths in VES VES-2,-6,-7 and VES VES-8. This were likely due to the resistivity characteristics between rock layers which entirely were the product of volcanic activity in the form of breksi, breksi Tuff, lava and tuff were not so different that less could be detected properly. The value of soil or rocks doty resistivity ranged from 0.5 to 868 Wm, volcanic breksi ranged from 1156 to 1944 Wm, volcanic breksi and aquifer I (shallow) ranged from 600 to 770 Wm, tuf ranged from 16 to 80 Wm, breksi Tuff and aquifer II (deep) ranged from 126 to 226 Wm. The possibility of the aquifer I (shallow) spreads were throughout the entire VES with the top depth ranged from 1.74 to 15.66 m. The base depth ranged from 14 to 28.59 m. The aquifer I thickness ranged from 8.37 to 16.36 m. The possibility of the aquifer II (deep) spreads were throughout the entire VES-2, VES-5, VES-6, and VES-7 with the top depth ranged from 17.16 to 72.32 m. The base depth ranged from 80 to 149.08 m. The aquifer I thickness ranged from 22,85 to 131,92 m. For the purposes of the water supply, it is recommended to perform the drilling around the VES-5, VES-6, VES-7 and VES-8 or by the VES-2 because in those areas have the potential of 2 aquifer layers or a thick aquifer layer. Keyword: Aquifer, groundwater, resistivity Abstrak Survey geolistrik ini untuk mendapatkan gambaran mengenai sebaran tahanan jenis (resistivitas lapisan batuan) baik secara vertikal maupun lateral, terutama sebaran lapisan batuan yang diduga dapat berfungsi sebagai lapisan pembawa air atau aquifer. Hasil survey ini diharapkan dapat memberikan data kepada PT. Sampoerna, tentang kemungkinan letak, keberadaan dan kedalaman lapisan pembawa air yang dapat dipergunakan untuk  memenuhi supply air bagi kebutuhan Integrated Education Trainning Center. Hasil pengukuran dari geolistrik secara umum tidak dapat mencapai target kedalaman yang harus disurvey, dimana dari 10 titik sounding yang dilakukan hanya terdapat 3 titik yang dapat menembus kedalaman >100 m yaitu pada VES-2, VES-6, VES-7 dan VES-8. Hal ini kemungkinan disebabkan karakteristik resistivitas antar lapisan batuan yang seluruhnya merupakan produk dari aktifitas vulkanik berupa breksi, breksi tuf, lava dan tuf ini tidak begitu berbeda sehingga kurang dapat terdeteksi dengan baik. Nilai resistivitas soil atau lapukan batuan berkisar antara 0.5–868 Wm, breksi vulkanik berkisar antara 1156–1944 Wm, breksi vulkanik dan aquifer 1 (dangkal) 600–770 Wm, tuf berkisar antara 16–80 Wm, breksi tuf dan aquifer 2 (dalam) berkisar antara 126–226 Wm. Kemungkinan sebaran dari aquifer 1 (dangkal) terdapat di seluruh VES dengan kedalaman top berkisar antara 1.74–15.66 m. Kedalaman base berkisar antara 14– 28.59 m. Ketebalan aquifer 1 berkisar antara 8.37-16.36 m. Kemungkinan sebaran dari aquifer 2 (dalam) terdapat di VES-2, VES-5, VES-6, dan VES 7 dengan kedalaman top berkisar antara 17.16–72.32 m. Kedalaman base berkisar antara 80 – 149.08 m. Ketebalan aquifer 1 berkisar antara 22,85 – 131,92 m. Untuk keperluan supply air, disarankan untuk melakukan pemboran disekitar VES-5, VES-6, VES-7 dan VES-8 atau didekat VES-2 karena pada daerah tersebut memiliki potensi 2 lapisan aquifer atau 1 lapisan aquifer yang tebal. Keyword: Aquifer, groundwater, resisivity Diterima: 06 September 2010 ; Disetujui:08 Februari 2011